2015
DOI: 10.1016/j.jnucmat.2014.11.087
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cleaning of ITER First Mirrors in magnetic field

Abstract: To avoid reflectivity losses in ITER's optical diagnostic systems, plasma sputtering of metallic First Mirrors is foreseen in order to remove deposits coming from the main wall (mainly beryllium and tungsten). Therefore plasma cleaning has to work on large mirrors (up to a size of 200×300 mm) and under the influence of strong magnetic fields (several Tesla). This work presents the results of plasma cleaning of aluminium and aluminium oxide (used as beryllium proxy) deposited on molybdenum mirrors. Using radio … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…In the case of ITER, the working temperature range of the divertor starts around 345 K, making our study fully relevant. Additionally, a better knowledge of tungsten properties (optical and mechanical) is needed in order to prevent security issues or failing of aerospace missions [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of ITER, the working temperature range of the divertor starts around 345 K, making our study fully relevant. Additionally, a better knowledge of tungsten properties (optical and mechanical) is needed in order to prevent security issues or failing of aerospace missions [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…The authors of [74,75] investigated the cleaning of a mirror surface from a deposit composed of Al, Al 2 O 3 , and W by the use of plasma with as working gas: Ar, Ne or a Ar+D 2 mixture. The most effective in this respect was the Ar plasma produced by a RF capacitively coupled discharge (at frequency 13.56 MHz) with the test mirror utilized as an electrode.…”
Section: Removal Of Deposited Filmmentioning
confidence: 99%
“…In some cases a full cleaning of deposits with initial reflectance restoration was achieved. For the first time a mirror with a size (98 mm in diameter) close to the size of a real first mirror in ITER was successfully cleaned from deposition by a 260 nm thick Al/Al 2 O 3 film on its surface [74]. This result is very important when considering the prospects for application of both these techniques (laser and plasma) to remove the contaminating layers from mirror surfaces in ITER environment.…”
Section: Removal Of Deposited Filmmentioning
confidence: 99%
“…It uses the mirror itself as the driven electrode, allowing good coupling of the cleaning plasma to the mirror surface, can build on the industrial experience with RF plasmas and has shown in lab experiments to be able to clean both small and large surfaces [7,8,10]. Also tests in magnetic field have been performed [11]. Figure 2 shows a sketch of the principle of RF discharge cleaning on the left and the total and diffuse reflectivity of both a pristine single crystalline molybdenum mirror (i.e.…”
Section: Jinst 11 P08010mentioning
confidence: 99%